Near-source characteristics of two-phase gas–solid outbursts in roadways - Zhou, Aitao; Zhang, Meng; Wang, Kai; Elsworth, Derek (International journal of coal science & technology, 2021)
Coal and gas outbursts compromise two-phase gas–solid mixtures as they propagate as shock waves and flows from their sources. Propagation is influenced by the form of the outburst, proximity to source, the structure and form of the transmitting roadways and the influence of obstacles. The following characterizes the propagation of coal and gas outbursts as two-phase gas–solid flows proximal to source where the coupled effects of pulverized coal and gas flows dominate behavior. The characteristics of shock wave propagation and attenuation were systematically examined for varied roadway geometries using experiments and numerical models. The results demonstrate that the geometry of roadway obstructions is significant and may result in partial compression and sometimes secondary overpressurization in blocked and small corner roadways leading to significant attenuation of outburst shock waves. The shock waves attenuate slowly in both straight and abruptly expanding roadways and more significantly in T-shaped roadways. The most significant attenuation appears in small angle corners and bifurcations in roadways with the largest attenuation occurring in blocked roadways. These results provide basic parameters for simplifying transport in complex roadway networks in the far-field, and guidance for the design of coal and gas outburst prevention facilities and emergency rescue.